Statutes of the Tropical Agricultural Research and Training Center; (approved at the First Meeting of the Board of Directors of CATIE held at Turrialba, Costa Rica, July 17-19, 1973) (CATIE, Turrialba (Costa Rica), 2014)
Disponible también ed. en Español